2013
DOI: 10.1289/ehp.1205921
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to the Pesticide DDT and Hypertension Diagnosed in Women before Age 50: A Longitudinal Birth Cohort Study

Abstract: Background: Elevated levels of the pesticide DDT (dichlorodiphenyltrichloroethane) have been positively associated with blood pressure and hypertension in studies among adults. Accumulating epidemiologic and toxicologic evidence suggests that hypertension during adulthood may also be affected by earlier life and possibly the prenatal environment.Objectives: We assessed whether prenatal exposure to the pesticide DDT increases risk of adult hypertension.Methods: We examined concentrations of DDT (p,p´- and o,p´-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…For example, prenatal exposure to the pesticide dichlorodiphenyltrichloroethane (DDT) is associated with increased medicated hypertension in adult women (La Merrill et al 2013), and prenatal exposure to its metabolite dichlorodiphenyldichloroethylene (DDE) is associated with elevated blood pressure in 4-year-old children (Vafeiadi et al 2015). However, whether the DDT or DDE burden in adults is associated with hypertension remains somewhat controversial because some studies do (Henríquez-Hernández et al 2014; Lind et al 2014; Siddiqui et al 2002), and some studies do not, report an association between DDT burden and hypertension in adult offspring (Goncharov et al 2011; Savitz et al 2014; Valera et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, prenatal exposure to the pesticide dichlorodiphenyltrichloroethane (DDT) is associated with increased medicated hypertension in adult women (La Merrill et al 2013), and prenatal exposure to its metabolite dichlorodiphenyldichloroethylene (DDE) is associated with elevated blood pressure in 4-year-old children (Vafeiadi et al 2015). However, whether the DDT or DDE burden in adults is associated with hypertension remains somewhat controversial because some studies do (Henríquez-Hernández et al 2014; Lind et al 2014; Siddiqui et al 2002), and some studies do not, report an association between DDT burden and hypertension in adult offspring (Goncharov et al 2011; Savitz et al 2014; Valera et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations between p,p -DDE and hypertension were described by Valera et al (2013) and Lind et al (2014). Moreover La Merrill et al (2013) found a positive association between prenatal exposure to DDT and hypertension. We found a gender difference with respect to the association between p,p -DDE and "Hypertension", similar to the gender difference found concerning "Diabetes", with only in men a significant positive association.…”
Section: Hypertensionmentioning
confidence: 91%
“…Fewer studies of environment contributions to CVD risks have focused on early-life exposures beyond the relationships with development of obesity. However, LAMERRILL et al [107] found that prenatal exposure to DDT and its metabolites was associated with an increased risk of hypertension at ages 37-47 years. A recent study that combined data from the Cardiovascular Risk in Young Finns study (Finland) with the Childhood Determinants of Adult Health Study (Tasmania, Australia) demonstrated that exposure to parental smoking during childhood or adolescence was associated with greater carotid intima-media thickness up to 25 years later [108].…”
Section: Cardiovascular Diseasementioning
confidence: 99%